A systematic review on failure modes and proposed methodology to artificially seed faults for promoting PHM studies in laboratory environment for an industrial gearbox. (April 2023) - Goswami, Priyom; Nandan Rai, Rajiv
Highlights: Failure modes of gearbox components like gears. shafts, bearings, seals, housing are investigated. Various literature on gearbox fault diagnosis, based on the failure modes of gears has been examined. Fault severity and prognostics studies on gear failures are reviewed. Failures of gearbox components, that have interaction ill effects on the gears are explored. Artificial seeding of fault in gears is proposed for simulating gear PHM studies in lab environment. Abstract: Gears are indispensable part of any industrial application. Gearbox have a rugged construction and are subjected to extremely harsh environmental conditions in industries, like high temperature, dust, excessive loading, humidity, chemical exposure etc. As a result, gears can fail much before reaching its designed life. In this paper, the authors have tried to explain failure modes and mechanisms of gears and gearbox components for undertaking research studies on industrial gearbox. A summary of gear failure modes with supported literature for fault diagnosis is tabulated for better understanding of the mechanics of fault with detection methods. A brief review on modulation-based models and dynamic based models for fault detection is also included in this work. Fault severity analysis and remaining useful life (RUL) prediction methods are reviewed and tabulated for complete understanding of the PHM framework. The current state of the research is also discussed for the diagnosis and prognosis of gear. As literature lacks a formalized way to replicate the failure modes and mechanisms to conduct prognostics and health management (PHM) studies on gearbox components in laboratory conditions, authors reviewed the existing literature and also proposes some techniques to artificially seed faults in components of gearbox. The work also includes a study on failure treatment of gearbox. Corrective and preventive maintenance strategies for gearbox failures are reviewed and proposed.